Development of porous COP–ceramic composites for application as low-relative-permittivity, low-dielectric-loss substrates in next-generation communication systems - Seisuke Ata; Takumi Ono; Yuto Kato (Scientific Reports)
Abstract Rapid advancements in communication technologies, such as the onset of 5G systems and the anticipated arrival of 6G systems, have increased the demand for materials with low relative permittivity ( $$ε_{r}$$ ) and dissipation factor (tanδ) to enable stable, low-power communication at higher frequencies. In this study, cycloolefin polymer (COP)-based composites containing an alumina (Al2O3) or aluminum nitride (AlN) filler were subjected to foaming by supercritical CO2 to introduce porosity, then evaluated as candidates for low- $$ε_{r}$$ , low-tanδ substrates. Their dielectric properties were evaluated over a large frequency range of up to ~ 120 GHz using the balanced-type circular disk resonator method. The results demonstrated that porosity effectively reduced $$ε_{r}$$ and tanδ without compromising the thermal properties; in particular, the COP–AlN composites exhibited $$ε_{r}$$ and tanδ values below 2.0 and 1 × 10–3, respectively. Furthermore, the $$\:{ε\:}_{r}$$ trend was consistent with effective medium theories, specifically the Maxwell–Garnett and Bruggeman models. Additional analyses of the thermal expansion and conductivities of the composites revealed enhanced compatibility with copper conductors, supporting the viability of these composites for next-generation communication devices.